Demonstration of Phase-Preserving Synchronization RFI Suppression for L-Band Spaceborne Bistatic Interferometric SAR - Yanyan Zhang; Junfeng Li; Pingping Lu; Tianyuan Yang; Robert Wang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Spaceborne bistatic synthetic aperture radar (BiSAR) systems utilize an intersatellite link to achieve phase synchronization. However, radio frequency interference (RFI) from communication satellites and ground-based radars often contaminates the synchronization signal, leading to inaccuracies in the inverted digital elevation model (DEM). Therefore, this article puts forward an advanced phase-preserving synchronization RFI suppression method and validates it using data from an $L$ -band BiSAR system, LuTan-1 (LT-1). The method involves detecting and locating RFI within a monopulse synchronization signal, and the signal at the estimated RFI position is removed to obtain a preprocessed signal. Then, based on the preprocessed signal and the RFI model, RFI is estimated using a gradient-based approach. Finally, the estimated RFI is subtracted from the monopulse signal to obtain the desired signal. In addition, synchronization RFI suppression and DEM generation experiments are performed on the LT-1 data to verify the proposed method. Experimental results demonstrate that the method effectively suppresses synchronization RFI and improves DEM accuracy, and it has extensive application prospects in future low-band distributed interferometric synthetic aperture radar missions.